Investigation of purifying bio-organic acid produced by Aspergillus niger - Koshikvel Verma, Valusamy (2025)
This study investigates the preparation and analysis of microbial media for the growth of Aspergillus niger, focusing on the effectiveness of potato dextrose broth (PDB) as a medium. The successful cultivation of A. niger in PDB was demonstrated through distinct morphological characteristics observed in both flasks, indicating effective adaptation and nutrient utilization by the fungus. The batch fermentation process revealed significant differences in fungal pellet development, influenced by factors such as nutrient availability, oxygen transfer, and agitation. The discovery of formic acid as a metabolic by-product underscores its potential industrial applications. The study also compared purification methods for formic acid, concluding that water distillation was the most effective technique due to its ability to separate contaminants based on boiling points without chemical interference. Although aluminium sulphate precipitation showed promise, it was less efficient and required additional purification steps. The findings suggest that optimizing fermentation parameters and exploring alternative purification methods could enhance formic acid production, contributing to the development of sustainable bioprocesses.